Autoimmune Regulator is required in female mice for optimal embryonic development and implantation†. Issue 6 (16th February 2019) - Warren, Bryce D; Ahn, Soo H; McGinnis, Lynda K; Grzesiak, Geoffrey; Su, Ren-Wei; Fazleabas, Asgerally T; Christenson, Lane K; Petroff, Brian K; Petroff, Margaret G
Abstract: Autoimmune Regulator (AIRE) regulates central immune tolerance by inducing expression of tissue-restricted antigens in thymic medullary epithelial cells, thereby ensuring elimination of autoreactive T cells. Aire mutations in humans and targeted Aire deletion in mice result in multiorgan autoimmune disease, known in humans as autoimmune polyglandular syndrome type 1 (APS-1). APS-1 is characterized by the presence of adrenal insufficiency, chronic mucosal candidiasis, and/or hypoparathyroidism. Additionally, females often present with gonadal insufficiency and infertility. Aire -deficiency (KO) in mice results in oophoritis and age-dependent depletion of follicular reserves. Here, we found that while the majority of young 6-week-old Aire -KO females had normal follicular reserves, mating behavior, and ovulation rates, 50% of females experienced embryonic loss between gestation day (GD) 5.5 and 7.5 that could not be attributed to insufficient progesterone production or decidualization. The quality of GD0.5 embryos recovered from Aire KO mice was reduced, and when cultured in vitro, embryos displayed limited developmental capacity in comparison to those recovered from wild-type (WT) mice. Further, embryos flushed from Aire KO dams at GD3.5 were developmentally delayed in comparison to WT controls and had reduced trophoblastic outgrowth in vitro. We conclude that AIRE does not play a direct role in uterine decidualization. Rather, reduced fertility of Aire- deficient females is likely due to multiple factors, including oophoritis, delayed preimplantation development, and compromised implantation. These effects may be explained by autoimmune targeting of the ovary, embryo, or both. Alternatively, altered embryonic development could be due to a direct role for AIRE in early embryogenesis. Abstract : Although mating and ovulation were normal, oocyte and embryo quality were reduced; peri-implantation embryonic loss was associated with reduced oocyte and embryo developmental potential in vitro.